Sedimentation and land cover change modeling of Magat Dam Watershed Area using remote sensing, geographic information system and cellular automata-markov analysis - Tupas, Mark Edwin A. (2012)
Dams and their reservoirs play critical roles in water resources management. However, their utility is threatened by sedimentation. While sedimentation naturally occurs in all reservoirs, too much of it results in decreased dam storage capacity. With degraded storage capacity; water flow control, flood control and power generation capabilities of dams decrease and dam operation lifespan is reduced. This paper uses land cover change and sediment modeling scheme to determine the remaining lifespan of the Magat dam reservoir in northern Philippines. To model land cover change, a stochastic approach using Markov analysis is implemented and is complemented by the use of Cellular Automata (CA) to account for spatial dependence. Satellite imageries of the Magat watershed for the years 2002, 2006, and 2010 are used in the CA-Markov Analysis to determine land cover transition rules. The modeled land cover change is then utilized in a Geographic Information System based Universal Soil Loss Equation-Sediment Delivery Ratio i order to generate sediment yield estimates. The estimates are compared with bathymetry data. The study shows a practical and dynamic framework for estrimating sedimentation and remaining useful years of dam reservoir.